Israiliyyat dalam Tafsir Jami’ul Bayan Karya Ibnu Jarir At-Thabari - Muhammad Roni Ritonga; Syukri (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
Tafsir Jami' al-Bayan by Ibn Jarir at-Thabari is one of the monumental works in the treasures of classical tafsir which is widely used as a reference by the mufassir afterwards. In it, at-Thabari collected various narrations from the companions, tabi'in, and early generation scholars, including those classified as Israiliyyat. This study aims to examine the form, source, and method of at-Thabari in addressing Israiliyyat in his tafsir, as well as its impact on the understanding of certain verses. Through a qualitative approach with the content analysis method, it is found that at-Thabari includes Israiliyyat in three forms: history that supports the interpretation, history as a complement to the story, and history that is rejected or criticized. Although at-Thabari does not explicitly reject all Israiliyyat, he often mentions sanads, compares several versions of the narrations, and shows a critical attitude towards narrations that are not in accordance with Islamic principles. This study concludes that the presence of Israiliyyat in at-Thabari's tafsir needs to be critically examined by contemporary readers, especially in distinguishing between scientifically acceptable narrations and those that come from unauthentic traditions outside Islam.